Solve for x y=xz+s

Math
y=xz+s
Rewrite the equation as xz+s=y.
xz+s=y
Subtract s from both sides of the equation.
xz=y-s
Divide each term by z and simplify.
Tap for more steps…
Divide each term in xz=y-s by z.
xzz=yz+-sz
Cancel the common factor of z.
Tap for more steps…
Cancel the common factor.
xzz=yz+-sz
Divide x by 1.
x=yz+-sz
x=yz+-sz
Move the negative in front of the fraction.
x=yz-sz
x=yz-sz
Solve for x y=xz+s

Download our
App from the store

Create a High Performed UI/UX Design from a Silicon Valley.

Scroll to top